El sobreendeudamiento y su impacto en el riesgo de crédito en instituciones microfinancieras peruanas: cajas municipales de ahorro y crédito 2016-2019 - Toledo Concha, Emerson Jesús (2021)
The micro and small business in Peru has been in constant development for 40 years, since then the Municipal Savings and Credit Banks (CMAC) appeared, which have administrative, financial, and economic autonomy and participate in the decentralization of the financial services; However, the growth of the loan portfolio is accompanied by high delinquency indicators related to the credit risk of these institutions. The objective of this work is to analyze whether the over-indebtedness of clients, measured as the balance and number of financial entities that the debtor has, is a variable that has a positive and direct relationship to credit risk, leading to the establishment of higher provisions that negatively affect in the income statements of this group of institutions. This research has a quantitative and correlational approach, where the data collected from 48 months, (2016-2019), were processed using the statistical methodology CRISP-DM, where the direct relationship of the over-indebtedness with the credit risk of the CMAC. The relevance of this research is aimed at making strategic decisions that allow better control of the payment behavior of your credit operations and this is reflected in better economic results.